PENGUKURAN TINGKAT KESADARAN MEREK (BRAND AWARENESS) PADA MOTOR HONDA (STUDI KASUS PADA MAHASISWA FAKULTAS ILMU SOSIA DAN ILMU POLITIK UNIVERSITAS RIAU) - Permadi, Giovani; Heriyanto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study was conducted to test the Brand Awareness Level Measurement (Brand Awareness) At Honda Motor (Case study of social, Faculty of Science and Political Science, University of Riau). Brand awareness measurement can be done by characterizing the four elements, namely, top of mind, brand recall, brand recognition, unaware of the brand. The sampling method used is convenience sampling that samples can be found easily, as many as 100 respondents.Analysis technique used is descriptive analysis, which can be interpreted as the troubleshooting procedures that are surrounded by depict or describe the circumstances, the subject or object of research at the present time based on the facts that appear or as it is. Data are presented in tabular form with the numbers percentage delengkapi with descriptions.From the calculation of the analysis we found that the motorcycle brand Honda took first place by 58% of respondents, brand recall brand motorcycle Honda finished second at 25%, the brand recognition of 80% indicating so familiar brands of motorcycles honda among consumers, the analysis unaware of brand honda motorcycle brands are not categorized within unaware of the brand for the majority of respondents know the brands of motorbikes honda.Keywords: Brand Awareness